Expression and Function of the Transient Receptor Potential Ion Channel Family in the Hematologic Malignancies - B. Morelli, Maria; Liberati, Sonia; Amantini, Consuelo; Nabiss, Massimo; Santoni, Matteo; Farfariello, Valerio; Santoni, Giorgio (Current Molecular Pharmacology, 2013)
Transient receptor potential (TRP) channels are important candidates mediating Ca2+ influx in excitable and nonexcitable cells such as normal and neoplastic hematopoietic tissues. They are non selective cation channels implicated in Ca2+ signaling in hematologic tumor cells. Here, we review the growing experimental evidence indicating that TRP channels should be included among the genes whose expression is altered in hematologic malignancies such as leukemias (AML, ALL, CML and CLL), B- and T-lymphomas and multiple myelomas (MM). These effects depend on the widespread roles played by the TRP channels in the modulation of the proliferation, differentiation and apoptosis of the hematopoietic cells. The analysis of the expression of the different TRP channels belonging to the TRPMs, TRPVs, TRPCs, TRPPs channel families expressed in different hematological malignacies, evidenced a widespread expression of TRPV2 channel in the myeloid and lymphoid leukemias, and a very peculiar expression of this channel in different types of B cell lymphomas and multiple myeloma, that is parallel to the restricted expression of TRPV2 in normal immune cells with respect to its presence in other human tissues. In vivo studies in children AML and ALL patients also evidenced the presence of a genetic polymorphism of the TRPM5 gene, that reduced the risk to develop leukemia in the children. Finally, the coexpression of TRPV5 and TRPV6 channels in lymphocytes, and their involvement in the radioresistance of K562 erythroleukemia cells to ionizing radiation exposure is of more interest. Thus in conclusion, the TRP channels represent promising targets for hematologic cancer therapy, and their exploitation may open to novel pharmaceutical and clinical approaches.
Keywords: Hematologic malignancies